Utility of rare disease registries in Latin America (2011)
There are many registries in Latin America as dialysis and kidney transplantation, breast cancer, primary immune deficiency, acute coronary syndromes, but the focus here are the registries of lysosomal storage diseases (LSD) because is our experience. Registry of Gaucher disease, Fabry disease, Pompe disease, and mucopolysaccharidosis type I are comprehensive observational voluntary programs that aim to collect clinical and laboratory data of initiation, progression, and evolution of those diseases, with and without treatment, using questionnaires of quality of life and/or skills and functions. There are two more programs of LSD: Hunter outcome survey and Fabry outcome survey. The registries are a kind of phase IV clinical trials, post marketing studies delineate additional information including the drug’s risks, benefits, and optimal use, and in addition we have data from natural history. The demographics of the Gaucher, Fabry, MPS I, and Pompe Registries show that a total of patients, being 16%, 8%, 15%, and 7%, respectively, of this population, and 19%, 19%, 18%, and 13%, respectively, of all physicians participating in the program are from Latin America. In the Gaucher Registry, we can observe that the percentage of children in Latin America (29%) is bigger than the rest of the world (20%), what can mean more severe disease in this population. These diseases are rare, and a database of clinical data from a larger number of patients gives us the opportunity to know about the natural history of these diseases, their phenotypic variability, and the response to specific enzyme replacement therapy in our population. © SSIEM and Springer-Verlag Berlin Heidelberg 2011.